Effects of dry-land strength and conditioning programs in age group swimmers - Amaro, N. M.; Marinho, D. A.; Marques, M. C.; Batalha, N.; Morouco, P. G. (The Journal of Strength and Conditioning Research, 2017)
Even though dry-land S&C training is a common practice in the context of swimming, there are countless uncertainties over its effects in performance of age group swimmers. The objective was to investigate the effects of dry-land S&C programs in swimming performance of age group swimmers. A total of 21 male competitive swimmers (12.7 ± 0.7 years) were randomly assigned to the Control group (n = 7) and experimental groups GR1 and GR2 (n = 7 for each group). Control group performed a 10-week training period of swim training alone, GR1 followed a 6-week dry-land S&C program based on sets and repetitions plus a 4-week swim training program alone and GR2 followed a 6-week dry-land S&C program focused on explosiveness, plus a 4-week program of swim training alone. Results for the dry-land tests showed a time effect between week 0 and week 6 for vertical jump (p < 0.01) in both experimental groups, and for the GR2 ball throwing (p < 0.01), with moderate to strong effect sizes. The time × group analyses showed that for performance in 50 m, differences were significant, with the GR2 presenting higher improvements than their counterparts (F = 4.156; p = 0.007; n2p=0.316) at week 10. Concluding, the results suggest that 6 weeks of a complementary dry-land S&C training may lead to improvements in dry-land strength. Furthermore, a 4-week adaptation period was mandatory to achieve beneficial transfer for aquatic performance. Additional benefits may occur if coaches plan the dry-land S&C training focusing on explosiveness.